Diversity and floristic composition of the dry and semideciduous forest of the Reserva Forestal Guanito, San Juan province, Dominican Republic - Lebrón-Liriano, Berleni V.; Guerrero Arias, Ángela (Instituto de Ecología, A.C., 2023)
Background and Aims: The flora of the dry forest of Cerros del Tabacal and the semi-deciduous forest of Loma del Agua of the Reserva Forestal Guanito in the Cordillera Central of the Dominican Republic, is presented. There are few species records of this reserve. Hence, the main objective was to inventory the vascular flora of both hills, and the specific objectives, to determine the diversity and richness of species in the Reserva Forestal Guanito and to document the biogeographic, conservation status, and life forms, and to register the floristic composition variation. Methods: Three plots of 10 × 10 m and two transects of 60 × 2 m were made on each hill, based on the species expression minimum area, and they were located in the areas with dense plant cover. The Shannon diversity index, Berger-Parker dominance index and Jaccard similarity coefficient were calculated. Key results: In the dry forest 81 species were recorded, distributed in 72 genera and 31 families; in the semi-deciduous forest, 110 species belonging to 96 genera and 50 families were registered. Fabaceae was the richest family in genera number on both hills (eight and nine, respectively), and Tillandsia the richest genus in species number (six and five, respectively). Tillandsia recurvata stands out with the highest abundance of individuals (173 individuals) in the dry forest, and Savia sessiliflora (39) in the semi-deciduous forest. The Shannon index showed that the semi-deciduous forest has more diversity than the dry forest, and the results of the Jaccard coefficient indicated that both hills have a highly differentiated floristic composition. Conclusions: This study reaffirms the importance and floristic richness of the forests of the Domincan Republic and at the same time constitutes the first floristic inventory for the Reserva Forestal Guanito.